Youth Well-Being in Brazil : An Index for Cross-Regional Comparisons - Dell'Aglio, Debora; Cunningham, Wendy; Koller, Silvia; Cassepp Borges, Vicente; Severo Leon, Joana (World Bank, Washington, DC, 2012)
This study constructs three indices to measure how well Brazil's young people are surviving their transition to adulthood. Youth development is difficult to quantify because of the multi-dimensionality of youth behavior. Most monitoring use individual indicators in specific sectors, making it difficult to track overall progress. The study adapts to the Brazilian case a methodology developed by Duke University to measure the well-being of U.S. children and youth. It uses readily available data to construct three indices for each Brazilian state based on 36 indicators encompassing the health, behavior, school performance, institutional connectedness, and socioeconomic conditions. The indices conclude that young people in the states of Santa Catarina and the Federal District are doing particularly well and those in Alagoas and Pernambuco are the worst off. While these rankings are expected to continue into the next generation, young people in other states have a brighter (Espiritu Santo) or more dismal (Rio Grande de Sul, Tocatins) future due to underinvestment in today's children. Still others (Rio de Janeiro) are underutilizing their resources so their young citizens are in a worse situation than they could be if the state were to invest more. The hope is that the methodology can be used in Brazil as it has been used in the United States to estimate the indices annually, thus allowing policymakers, young people, and society to track the well-being of youth in each state over time.